Frequency-Dependent Higher Moment Risks - Jozef Barunik; Josef Kurka (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Based on intraday data for a large cross-section of individual stocks and Exchange traded funds, we show that short-term as well as long-term fluctuations of realized market and average idiosyncratic higher moments risks are priced in the crosssectionof asset returns. Specifically, we find that market and average idiosyncratic volatility and kurtosis are significantly priced by investors mainly in the long-run even if controlled by market moments and other factors, while skewness is mostly short-run phenomenon. A conditional pricing model capturing the time-variation of moments confirms downward-sloping term structure of skewness risk and upwardsloping term structure of kurtosis risk, moreover the term structures connected to market skewness risk and average idiosyncratic skewness risk exhibit different dymanics.
Keywords: C14; C22; G11; G12; 330; Higher Moments; frequency; Spectral Analysis; Cross-sectional